Pengembangan Instrumen Penilaian Non Tes Kurikulum Merdeka Pada Pendidikan Dasar: Development of Non Test Instruments in The Independent Curriculum - Sufya, Sulfina; Atho’urrohman, Wifqi; Zuriyah, Indah Aminatuz; Basith, Abdul (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Assessment is important in a learning process, with the teacher’s assessment will know the ability of students in learning activities. Assessment of the independent curriculum requires teachers as educators not only to know the abilities of students related to cognitive but also psychomotor and affective. Therefore the research objective is to carry out the development of non-test assessments in PAIBP subjects, using library research research methods. Collect various references regarding non-test assessment instruments/devices and compile examples of non-test assessment instrument formats in the independent curriculum that can be used in PAIBP lessons.